Tanzania Economic Update, April 2017 : Money Within Reach - Extending Financial Inclusion in Tanzania - World Bank Group (World Bank, Washington, DC, 2017)
In 2016, the global economic environment remained subdued, with growth performance in Sub-Saharan Africa the weakest in over 20 years. Economic conditions across most advanced economies remained challenging, while emerging and developing economies as a whole are set to maintain their growth momentum. However, there is a lot of variation between developing countries. Growth in Sub-Saharan Africa slowed down significantly, dropping from an average real GDP growth rate of 4.5 percent in the 2010-15 period to an estimated 1.5 percent in 2016, the lowest rate in more than two decades. The decline in the region's average growth rate is the result of a number of factors, most notably the ongoing adjustments to sluggish commodity prices, the slowdown in export demand, and the tightening of global financial conditions. In the context of these developments, the ninth edition of the Tanzania Economic Update describes the current state of the economy, with the special topic focusing on financial inclusion. The report aims to stimulate policy analysis and debate around the key economic and development challenges that Tanzania faces as it strives to fulfill its aspirations of becoming a middle-income country. In addition to describing key aspects of macroeconomic performance and fiscal management, the report presents a timely analysis of the impact of financial sector deepening on economic activity and on the livelihoods of Tanzanians.